PENGARUH KOMITMEN CSR TERHADAP LOYALITAS KONSUMEN MELALUI KEPERRCAYAAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Nasabah Bank Rakyat Indonesia) - Hadi H, Abdul; Apriliana, Iin; Affan, Junaidi (Sekolah Tinggi Ilmu Ekonomi SBI, 2024)
In the era of advanced and modern globalization, people are required to be more selective in choosing banking products. On the other hand, banks must be able to maintain their marketshare. One way to seize the market is with CSR programs. BRI as one of the largest banks in Indonesia has a CSR program with the hope of increasing customer loyalty. The purpose of this study is todetermine the influence between CSR commitment to consumer loyalty through trust intervening variables.This study used quantitative methods with the research population of BRI customers. This study has several variables, namely the influence of CSR commitment (X) as an independent variable, consumer loyalty (Y) as a dependent variable, and trust as a mediating or intervening variable. This research involved 150 BRI customer respondents in Klaten Regency. Based on the results of hypothesis testing, it can beconclude dthat: 1) CSR commitment has a direct effect on consumer loyalty with an estimate regression weight coefficient value of 0.164 and a C.R. value of 2.117. The significance test between variable (X) andvariable (Y) shows a probability valueof 0.034 (p < 0.05). 2) Trust has a direct effect on consumer loyalty with an estimate regression weight coefficient value of 0.740 and a C.R. value of 7.799. The significance test between variable (Z) and variable (Y) shows a probability valueof 0.000 (p < 0.05). 3) CSR commitment has a direct effect on Trust with an estimate regression weight coefficient value of 0.726 and a C.R. value of 7.931. The significance test between variable (X) andvariable (Y) shows a probability valueof 0.000 (p < 0.05). 4) the effect ofthe mediation variable was tested usingthe Sobel test with t calculated resultsof 2.031 > 1.96 with a signification level of 0.000 < 0.05. These results show that variable (X) has a positive influence on variable (Y) and mediating variable has a positive and significant influence on variable (X) and variable (Y). So, CSR commitment can affect consumer loyalty through intervening variables, namely BRI customertrust. Keyword : Li festyle, consumer buying interest, trend, product knowledge.